Data assimilation on mechanistic models of glucose metabolism predicts glycemic states in adolescents following bariatric surgery - Richter, Lauren R.; Albert, Benjamin I.; Zhang, Linying; Ostropolets, Anna; Zitsman, Jeffrey L.; Fennoy, Ilene; Albers, David J.; Hripcsak, George (Frontiers in Physiology, 2022)
Type 2 diabetes mellitus (T2DM) is a complex and under-treated disorder closely intertwined with obesity. Adolescents with severe obesity and T2DM have a more aggressive disease compared to adults, with a rapid decline in pancreatic  cell function and increased incidence of comorbidities. Given the relative paucity of pharmacotherapies, bariatric surgery has become increasingly used as a therapeutic option. However, subsets of this population have sub-optimal outcomes, with either inadequate weight loss or little improvement in disease. Predicting which patients will benefit from surgery is a difficult task and detailed physiological characteristics of patients who do not respond to treatment are generally unknown. Identifying physiological predictors of surgical response therefore has the potential to reveal both novel phenotypes of disease as well as therapeutic targets. We leverage data assimilation paired with mechanistic models of glucose metabolism to estimate pre-operative physiological states of bariatric surgery patients, thereby identifying latent phenotypes of impaired glucose metabolism (IGM). Specifically, maximal insulin secretion capacity, , and insulin sensitivity, SI, differentiate aberrations in glucose metabolism underlying an individual’s disease. Using multivariable logistic regression, we combine clinical data with data assimilation to predict post-operative glycemic outcomes at 12 months. Models using data assimilation sans insulin had comparable performance to models using oral glucose tolerance test glucose and insulin. Our best performing models used data assimilation and had an area under the receiver operating characteristic curve of 0.77 (95% CI 0.7665, 0.7734) and mean average precision of 0.6258 (0.6206, 0.6311). We show that data assimilation extracts knowledge from mechanistic models of glucose metabolism to infer future glycemic states from limited clinical data. This method can provide a pathway to predict the long-term, post-surgical glycemic states by estimating the contributions of insulin resistance and limitations of insulin secretion to pre-operative glucose metabolism.